Pengembangan Sistem Informasi Dalam Mempromosikan UMKM Berbasis Digital Pada Kelurahan Ogan Baru Kota Palembang - Hidayat, Kemas Muhammad Wahyu (Jurnal Nasional Ilmu Komputer, 2025)
The rapid development of information technology has transformed the business landscape, including the Micro, Small, and Medium Enterprises (MSMEs) sector. Digital technology opens up significant opportunities for MSMEs to increase their competitiveness through broader and more efficient promotion and marketing. However, in Ogan Baru Village, Palembang City, MSMEs still face challenges in optimally utilizing this technology, particularly due to limited access to promotions. This research aims to develop a digital-based information system designed to promote MSME products while addressing the need for easy-to-use and affordable technology solutions. The research method used a waterfall-based systems development approach, encompassing the stages of needs analysis, system design, implementation, testing, and evaluation. Primary data was collected through interviews with MSMEs in Ogan Baru Village, while secondary data was obtained from relevant literature. The developed system is an interactive digital platform that enables MSMEs to publish products, manage business information, and utilize analytical features to evaluate marketing strategies. The results indicate that this information system is effective in increasing the visibility and efficiency of MSME promotions. Testing revealed that 85% of users felt that the platform significantly improved market access and reduced promotional costs compared to traditional methods. This system also facilitates the management of product information in real time. In conclusion, the development of a digital-based information system provides a relevant and sustainable solution for MSMEs in facing the challenges of the digital era. This research makes a significant contribution to MSME digitalization strategies and serves as a model for implementation in other regions. Further development is recommended for the integration of additional features such as online payments and personalized promotions based on customer data